Campaigning Zakat on Social Media: The Role of Message Strategies in the Decision to Pay Zakat - Juliana Nasution; Nurhayati Nurhayati; Marliyah Marliyah (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
Zakat campaigns in Indonesia have utilized social media as a platform to address various zakat management problems. This research examines the message strategies used by zakat institutions in their campaigns on social media. Messages are an important component in the success of a campaign to influence the voluntary behavior of campaign targets. The message strategy theory applied in this study refers to Tafesse and Wien, including informational, transformational, and interactional messages. This research uses a quantitative approach, employing muzakki zakat in Dompet Dhuafa Waspada, North Sumatra, as the respondents. Data analysis technique used the SEM-PLS approach with SmartPLS 4.0 software. The research results show that the informational and transformational variables had a significant effect on the decision to pay zakat. Meanwhile, the interactional variables had no significant effect on the decision to pay zakat. Therefore, the role of message strategy in zakat campaigns on social media is important to increase zakat fundraising.